Pump−probe experiments at the TEMPO beamline using the low‐α operation mode of Synchrotron SOLEIL. (15th June 2017) - Silly, Mathieu G.; Ferté, Tom; Tordeux, Marie Agnes; Pierucci, Debora; Beaulieu, Nathan; Chauvet, Christian; Pressacco, Federico; Sirotti, Fausto; Popescu, Horia; Lopez-Flores, Victor; Tortarolo, Marina; Sacchi, Maurizio; et al.
Abstract : The low‐α operation mode of SOLEIL is presented and gives the operation details for experiments using soft X‐rays at the TEMPO beamline. Experiments are presented to give the reader the possibility to evaluate the performances of the installation. With the increasing research activity using time‐resolved experiments it should be interesting for the synchrotron radiation community. It is thought that the low‐α mode operation is the natural bridge between the usual time scale of synchrotron pulses and laser‐driven femtosecond experiments. Abstract : The SOLEIL synchrotron radiation source is regularly operated in special filling modes dedicated to pump–probe experiments. Among others, the low‐α mode operation is characterized by shorter pulse duration and represents the natural bridge between 50 ps synchrotron pulses and femtosecond experiments. Here, the capabilities in low‐α mode of the experimental set‐ups developed at the TEMPO beamline to perform pump–probe experiments with soft X‐rays based on photoelectron or photon detection are presented. A 282 kHz repetition‐rate femtosecond laser is synchronized with the synchrotron radiation time structure to induce fast electronic and/or magnetic excitations. Detection is performed using a two‐dimensional space resolution plus time resolution detector based on microchannel plates equipped with a delay line. Results of time‐resolved photoelectron spectroscopy, circular dichroism and magnetic scattering experiments are reported, and their respective advantages and limitations in the framework of high‐time‐resolution pump–probe experiments compared and discussed.